Footprints under the window - Dixon, Franklin W. (New York : Grosset & Dunlap, 1993)
Frank and Joe uncover a plot to steal a vital top-secret instrument of the space program.
6.5
5-8
Keywords: Mystery and detective stories; Mystery fiction